“Evaluación de dosis de fertilización NPK en el cultivo de maíz híbrido AG-612 bajo condiciones de riego complementario en el distrito de buenos aires- San Martín” - Castre Ramírez, John (2002)
The present project was developed between march and july 2000, in Buenos Aires Distric, Picota Province (San Martín región), Perú, South América; located in 76º22'55" west longitude and 06º 22' 15" South latitude and 215 meters above sea level. We worked eiht "corn" (AG - 612 hybrid) and three NPK fertilizer dose under conditions of "complementary watering". The costs of production and treatments and relation between "benefits/cost" have also been vegetative characteristics have been determined as well. We used a "statistic block design" absolutly "ramdomized"; the factorial arrangement was 3x3x3 with 27 treatments and three repetitions each treatment which results were verified by "variance analysis", the Duncan test and the variability coeficient. The experimental soil was loamy soil, having pH 8.16 of alkaline reaction, with high contains of organic material (4.43%), the average contents of phosphorus was 16.0 ppm, and the interchangable potasium contents was 0.62 meq/100 Gr. The tradtional way for planting was used, in dry soil, 0.85 m., distance between furrows and 0.50 m among plans, leaving a distance of three plants each "blow'', which makes a density of 60,000 plants/hectare. The cultivation was four times watered by "dispersion system" and fertilization Was made . I using different levels: firts, Low: 120-20-30, medium: 140-46-50, and high level: 160-80-80. And, on the 1oth day after planing, it was urgent to add half dose of nitrogen and a full phosphorus dose. The second dose of nitrogen was add 30 days after planting. According to the results of the statistical analysis it was found that the best dose of fertilizer was the T13(140-46-30) at 14% of humidity which produce an average of 7,455 Kg of corn per hectare. The T13 (140-46-30) followed by the T1(120·20-30) and T10(140-20-30) with related values of BIC: firts: 1.21; second: 1.20; third: 1.19 respectively. The economic benefits of these cultivations reporta SI. 461.00 Nuevos Soles (Peruvian currency) (that is to say $ 134 Amerívcan Dollars, echange rate: 3.44; may 2002), per harvest campaíng, in the first case. In the second case. In the second case, SI. 404.07 Nuevos Soles (Per'uvian currecy) (or $ 117 American Dollars, at the same exchange rate). In the thírd case, ít was SI. 400.12 Nuevos Soles (or $ 116 American Dollars,_ same exchange rate). Thanks to the treatments we hadan important economíc benefit.